The Odyssey of Ibn Battuta : uncommon tales of a medieval adventurer - Waines, David; Ibn Batutta , 1304-1377 (New York : I.B. Tauris, 2010)
"Ibn Battuta was, without doubt, one of the world's truly great travellers. Born in fourteenth-century Morocco and contemporary of Marco Polo, Ibn Battuta has left us an account in his own words of his remarkable journeys throughout the Islamic world and beyond. ... David Waines discusses [Ibn Battuta's work], life, and times ..."-- Jacket.
1. travel tales, their creators and critics -- 2. The travel -- 3. Tales of food and hospitality -- 4. Tales of sacred places, saints, miracles and marvels -- 5. Tales of the 'other'
Also published: Chicago : University of Chicago Press, 2010
Includes bibliographical references and index
Keywords: Ibn Batutta, -- 1304-1377.; Ibn Batutta, -- 1304-1377 -- Travel -- Islamic Empire; Travel, Medieval; Travelers -- Islamic Empire -- Biography; Islamic Empire -- Description and travel -- Early works to 1800